RIA: a one-stop virtual platform for research-related resources in FSG - UiTM, Faculty of Applied Sciences (Faculty of Applied Sciences, 2021)
RIA is a web page created by the Office of Research, Industry, and Alumni, Faculty of Applied Sciences (FSG).